2022
DOI: 10.1111/cpr.13249
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell sequencing reveals the heterogeneity and intratumoral crosstalk in human endometrial cancer

Abstract: Background Endometrial cancer (EC) is one of the most common gynecologic malignancies with increasing morbidity. Cell–cell and cell‐matrix interactions within the tumour microenvironment (TME) exert a powerful influence over the progression of EC. Therefore, a comprehensive exploration of heterogeneity and intratumoral crosstalk is essential to elucidate the mechanisms driving EC progression and develop novel therapeutic approaches. Methods 4 EC and 2 normal endometrium samples were applied for single‐cell RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Recent applications of single-cell transcriptome analysis in gynecological cancers include elucidating the heterogeneity of the disease, collecting microenvironmental data, elucidating drug resistance mechanisms, and enhancing cancer diagnostic and treatment approaches [ 46 ]. Previous research found that EC cells could be classified into several cell types: epithelial cells, fibroblasts, immune cells, and endothelial cells [ 47 ]. However, an in-depth analysis of epithelial EC cells at the single-cell level is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications of single-cell transcriptome analysis in gynecological cancers include elucidating the heterogeneity of the disease, collecting microenvironmental data, elucidating drug resistance mechanisms, and enhancing cancer diagnostic and treatment approaches [ 46 ]. Previous research found that EC cells could be classified into several cell types: epithelial cells, fibroblasts, immune cells, and endothelial cells [ 47 ]. However, an in-depth analysis of epithelial EC cells at the single-cell level is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These may be related to poor prognosis. Previous studies have shown that fibroblasts maintain frequent communication with cancer cells to promote the development of endothelial cancer ( Yu et al, 2022 ). We also found FANCE is predominantly expressed in fibroblasts and correlated with poor prognosis in endometrial cancer according to scRNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The attached fibroblasts are washed and incubated at 37 °C in a tissue culture medium. In addition to generating primary fibroblasts de novo, many fibroblast cell lines from multiple etiologies and organs of origin are available as well from commercial sources [ 61 , 74 , 75 , 76 ].…”
Section: Normal Tissue Fibroblastsmentioning
confidence: 99%
“…Once purified, CAFs and NFs can be analyzed for molecular differences using a variety of standard, population-averaged molecular techniques, including gene expression microarrays and RNAseq, as well as single-cell RNAseq technology [ 69 , 70 , 76 ]. In addition, fibroblasts can be imaged in situ using an array of in situ sensors [ 83 ].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation